Advances in human factors in training, education, and learning sciences : proceedings of the AHFE 2018 International Conference on Human Factors in Training, Education, and Learning Sciences, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: proceedings of the AHFE 2018 International Conference on Human Factors in Training, Education, and Learning Sciences, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. (2019) - Unknown
No abstract available